Strategi Inovasi Pembelajaran Pendidikan Agama Islam Anak Usia Dini - Ulfa Ulfa (SELING: Jurnal Program Studi PGRA, 2019)
Islamic education is expected to develop a systematic pattern of thinking to foster a creative and high integrity Muslim person so that they are able to adapt to changes that occur in society. Islamic education must start since childhood. A dynamic educational process requires innovation. So innovation is very important in education, the strategy of education innovation is done to solve the problem of education, one of the educational innovations that should not be abandoned is to follow the life of the people and the culture of mankind, which is now the information age, in the context of Islamic religious education in early childhood going well and will produce a positive and better, if the education practitioners understand some strategies of education and teaching innovation in Islamic Education